2001
DOI: 10.1161/hs1001.096613
|View full text |Cite
|
Sign up to set email alerts
|

Role of Conventional Angiography in Evaluation of Patients With Carotid Artery Stenosis Demonstrated by Doppler Ultrasound in General Practice

Abstract: Background and Purpose-Previous studies have suggested that patients with carotid stenosis who are candidates for endarterectomy can be effectively identified on the basis of carotid Doppler ultrasound alone. Before widespread acceptance of this policy, the accuracy of carotid Doppler ultrasound outside selected centers and clinical trials needs to be evaluated. We performed a 12-month prospective study to evaluate the accuracy of Doppler ultrasound in identifying patients for carotid intervention in general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 22 publications
(26 reference statements)
1
27
2
5
Order By: Relevance
“…We report a high accuracy rate of carotid DUS when performed in the SPC. The misclassification rate in our study for symptomatic stenosis (50-99%) was 2.2 % (95%CI: 0 -6.5%), and overall 1.45% (95%CI: 0 -4.3%), which is much lower than the recently reported misclassification rate of 28% 8 and the false positive rate of 20% 12 . The wide variation in the reported accuracy rates of DUS cannot solely be explained on the basis of difference in the experience or skill of the technologist, because all these studies were carried out in institutions where DUS imaging is performed by fully trained and accredited ultrasonographers.…”
Section: Volume 32 No 3 -August 2005contrasting
confidence: 88%
See 2 more Smart Citations
“…We report a high accuracy rate of carotid DUS when performed in the SPC. The misclassification rate in our study for symptomatic stenosis (50-99%) was 2.2 % (95%CI: 0 -6.5%), and overall 1.45% (95%CI: 0 -4.3%), which is much lower than the recently reported misclassification rate of 28% 8 and the false positive rate of 20% 12 . The wide variation in the reported accuracy rates of DUS cannot solely be explained on the basis of difference in the experience or skill of the technologist, because all these studies were carried out in institutions where DUS imaging is performed by fully trained and accredited ultrasonographers.…”
Section: Volume 32 No 3 -August 2005contrasting
confidence: 88%
“…A previous study in 1987 reported a sensitivity of 96%, specificity of 95% and accuracy rate of 95% in 62 patients with an occluded artery demonstrated by duplex scanning. 13 In a more recent study, out of 16 patients with DUS diagnosed complete occlusion, two had stenosis of 70-99% on a subsequent angiogram 12 . This variation in reported diagnostic accuracy of DUS in differentiating between a tight stenosis and complete occlusion has resulted in angiographic confirmation of the ultrasound findings, a widely accepted practice.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Entretanto, Qureshi e cols. 22 observaram que o ultra-som apresentou falso positivo de 20% para estenoses > 50% em pacientes sintomáticos e falso positivo de 41% para estenoses < 60% em pacientes assintomáticos. Assim, é recomendada, antes de tomar a devida conduta, realizar angiografia de carótidas nos pacientes cujo ultra-som detectou estenose > 50% 22 .…”
Section: E Tab Iii)unclassified
“…22 observaram que o ultra-som apresentou falso positivo de 20% para estenoses > 50% em pacientes sintomáticos e falso positivo de 41% para estenoses < 60% em pacientes assintomáticos. Assim, é recomendada, antes de tomar a devida conduta, realizar angiografia de carótidas nos pacientes cujo ultra-som detectou estenose > 50% 22 . Como alternativa para esse subgrupo, foram estudados 92 pacientes com evidências clí-nicas e ultra-sonográficas de estenose, utilizando ressonância nuclear magnética tridimensional contrastada comparada à angiografia com subtração digital, obtendo-se uma sensibilidade, especificidade e acurácia de 97%, 82% e 92,5% respectivamente 23 .…”
Section: E Tab Iii)unclassified